2013
DOI: 10.1097/iae.0b013e318285cb71
|View full text |Cite
|
Sign up to set email alerts
|

Lucedex

Abstract: The LuceDex pilot study suggested a possible benefit of adding intravitreal dexamethasone to treatment of neovascular age-related macular degeneration with intravitreal ranibizumab. A larger study is needed to further identify and define possible benefits of this combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In particular, it has been shown that intravitreal combination of triamcinolone and bevacizumab is highly efficient in decreasing the amount of subretinal fluid, limiting neovascularization and preserving or increasing visual acuity32. Similar positive results were obtained in a recent study of combined intravitreal ranibizumab and dexamethasone33.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, it has been shown that intravitreal combination of triamcinolone and bevacizumab is highly efficient in decreasing the amount of subretinal fluid, limiting neovascularization and preserving or increasing visual acuity32. Similar positive results were obtained in a recent study of combined intravitreal ranibizumab and dexamethasone33.…”
Section: Discussionsupporting
confidence: 88%
“…The LuceDex study 21 was the first study using the IV DEX injections (500 mg in 0.05 mL), followed by IV ranibizumab (4 monthly injections of 0.5 mg in 0.05 mL) that was compared with IV ranibizumab monotherapy (Group 2; total 37 patients). After 4 consecutive months, in both groups, ranibizumab pro re nata treatment was administered if signs of lesion activity were present.…”
Section: Namdmentioning
confidence: 99%
“…Certainly, many reports have suggested that switching patients to Aflibercept which blocks multiple angiogenic growth factors including VEGF-A, VEGF-B and PIGF (placental growth factor) have better treatment outcomes than anti-VEGF monotherapy78. In addition, combination therapy with anti-VEGF and corticosteroid has better treatment outcomes than anti-VEGF monotherapy910. There is currently great research interest in discovering new angiogenic pathways that may serve as therapeutic targets to achieve better outcomes in the treatment of nAMD in the future.…”
mentioning
confidence: 99%